SOA characterization for and logic operation on SOA based NOLM - Mohd Farizal, Faridus; Mohamad Halim, Abd Wahid; Norhayati, Sabani; Rosnahlizawati, Rostam (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/